Control of an aquarium pump using android-based device - Satis Muthusamy (2023)
In order to regulate the water in tank, an aquarium pump is surely needed. Besides, a proper selection of aquarium water pump is essential in order to have a better flow-rate which allows the inline filtration system to work its best.